2014
DOI: 10.1007/978-3-319-08245-5_19
|View full text |Cite
|
Sign up to set email alerts
|

Visual vs. DOM-Based Web Locators: An Empirical Study

Abstract: Automation in Web testing has been successfully supported by DOMbased tools that allow testers to program the interactions of their test cases with the Web application under test. More recently a new generation of visual tools has been proposed where a test case interacts with the Web application by recognising the images of the widgets that can be actioned upon and by asserting the expected visual appearance of the result.In this paper, we first discuss the inherent robustness of the locators created by follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 16 publications
1
43
0
1
Order By: Relevance
“…Maintenance costs that are discussed theoretically and presented through qualitative observations from industrial projects (Karhu et al 2009;Berner et al 2005). Some empirical research on maintenance costs have been reported but for open source software (Leotta et al 2013(Leotta et al , 2014Nguyen et al 2014) whilst the number of papers that include industrial systems are limited (Sjösten-Andersson and Pareto 2006).…”
Section: Related Workmentioning
confidence: 99%
“…Maintenance costs that are discussed theoretically and presented through qualitative observations from industrial projects (Karhu et al 2009;Berner et al 2005). Some empirical research on maintenance costs have been reported but for open source software (Leotta et al 2013(Leotta et al , 2014Nguyen et al 2014) whilst the number of papers that include industrial systems are limited (Sjösten-Andersson and Pareto 2006).…”
Section: Related Workmentioning
confidence: 99%
“…These approaches offer different payoffs in terms of maintenance [Leotta et al 2014]. Location maintenance is addressed through both preventive and curative approaches (see Grace et al [2011] for an overview).…”
Section: Maintainabilitymentioning
confidence: 99%
“…These auto-generated keywords will be used later by the automation framework to test the SUT. The main issue in this solution is that output test steps from the English written test cases are not 100% guaranteed to be correct because the user can express a test case in many different forms [36]. This requires human intervention to revise the auto-generated steps before running them.…”
Section: Fig 4 Hybrid Testing Frameworkmentioning
confidence: 99%